THE SHELF LIFE OF HERBAL TEA FROM BELIMBING WULUH (AVERRHOA BILIMBI L.) IS A FUNCTIONAL FOOD FOR TREATING HYPERTENSION : UMUR SIMPAN TEH HERBAL DAUN BELIMBING WULUH (Averrhoa Bilimbi L.) PANGAN FUNGSIONAL PENANGGULANGAN HIPERTENSI - Magfirah Magfirah Ramadani; Abdul Salam; Nurzakiah; Nurhaedar Jafar; Safrullah Amir (Departement of Nutrition, Faculty of Public Health, Hasanuddin University, Makassar, 2023)
Introduction: Hypertension is also called a